2008
DOI: 10.1080/14616730802113737
|View full text |Cite
|
Sign up to set email alerts
|

Childhood temporary separation: long-term effects of the British evacuation of children during World War 2 on older adults' attachment styles

Abstract: This study investigates long-term effects on adult attachment due to temporary childhood separation as a result of the British evacuation of children during World War 2. A total of 859 respondents, aged 62-72 years, were recruited who had childhood homes in the county of Kent during the war. Of these, 770 had been evacuated and 89 remained at home and formed a non-evacuated control group. They participated in this retrospective survey of possible associations between childhood experiences of the evacuation, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
(15 reference statements)
5
23
0
Order By: Relevance
“…These respondents would have developed a working model of attachment based on their experiences of separation that has influenced their style of attachment and dependency through life. This is supported by the results of the attachment study by Rusby and Tasker (2008), using the same respondent sample, which found that 25% of those evacuated in early childhood, aged 4-6 years, were in the fearful attachment style category, as defined by the Relationship Questionnaire of Bartholomew and Horowitz (1991). A comparison of these results with those of the current study has shown that the fearful attachment style was significantly correlated with the incidence of depression (r ¼ 0.43).…”
Section: Implications For Attachment Theorysupporting
confidence: 86%
See 4 more Smart Citations
“…These respondents would have developed a working model of attachment based on their experiences of separation that has influenced their style of attachment and dependency through life. This is supported by the results of the attachment study by Rusby and Tasker (2008), using the same respondent sample, which found that 25% of those evacuated in early childhood, aged 4-6 years, were in the fearful attachment style category, as defined by the Relationship Questionnaire of Bartholomew and Horowitz (1991). A comparison of these results with those of the current study has shown that the fearful attachment style was significantly correlated with the incidence of depression (r ¼ 0.43).…”
Section: Implications For Attachment Theorysupporting
confidence: 86%
“…Those evacuated in adolescence had significantly lower lifetime incidences of both depression and clinical anxiety than those evacuated at a young age; and those who received good foster care during evacuation were at a reduced risk of such affective disorders in adulthood. These quantitative results relating to lifespan, mental health have supported the conclusions from the earlier qualitative work where participants perceived the effect of their individual experience in developmental terms, ranging from providing confidence and 'widened horizons' at the positive end through to leaving an 'emotional legacy' at the negative end (Rusby, 2005).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations